O que é uma habitação rural sustentável? desenho de um protótipo e conceitualização do termo - Pérez Pinilla, Felipe Emiliano (2020)
This text is inscribed in the field of architecture and sustainable rural development. The object studied and designed to be sustainable is rural housing and those who will directly benefit from this project are the rural communities in the municipality of Tena Cundinamarca, Colombia. To this end, we carried out bibliographic and documentary research, applied questionnaires and made a wide survey of architectural possibilities from a set of sustainable variables previously selected to, in the last chapter, present our proposal for sustainable rural housing.